Compliance of pre-packaged food products with Nigerian food labelling guidelines: the NigeFE study - Iheme, Gideon Onyedikachi; Egechizuorom, Ifeoma Mercy; Edafioghor, Linda Obianuju; Okonkwo, Elizabeth Monday; Olah, Linda Eneh; Onyeonu, Barbara Adimchinobi; Kupoluyi, Oluwadamilare Emmanuel; Enuka, Hannah Chinyere; Adile, Adimchi Dike; Hajara, Idris; Ogbonna, Obinna Chimela; Asouzu, Nwabuma Cynthia; et al. (Frontiers in Nutrition, 2025)
BackgroundFood labelling policy has become increasingly important in public health due to the rising burden of diet-related diseases. This study examines the compliance of pre-packaged foods sold in Nigerian markets with national food labelling guidelines.MethodsA total of 883 pre-packaged foods from broad categories were purposively enlisted from selected Nigerian stores and supermarkets. Food label information was evaluated against eleven (11) requirements stipulated by the National Agency for Food and Drug Administration and Control (NAFDAC) and components of the International Network for Food and Obesity/Non-communicable Diseases Research, Monitoring and Action Support (INFORMAS). Descriptive statistics and multiple linear regression were applied to assess compliance levels and their associated determinants.ResultsThe majority (>70.0%) of the pre-packaged foods complied with key labelling requirements except quantitative ingredient declaration (39.1%) as well as nutrient declaration of priority (56.5%), and non-priority (38.1%) nutrients. Overall, a mean food label compliance score of 9.19 + 1.43 out of a possible 11.0 was recorded. The inclusion of supplementary nutrition information and the declaration of non-priority nutrients in pre-packaged foods were each significantly (p < 0.01) associated with approximately a 0.50-point higher compliance score with national food labelling guidelines than pre-packaged foods lacking this information.ConclusionHigh compliance with the guidelines was reported; however, the declarations of nutrient and quantitative ingredients were not sufficiently met. Prioritizing food labelling in policy formulation, alongside targeted support for food manufacturers particularly local producers will help address existing gaps across the food compliance spectrum.